Isolation of turbinaric acid as a chemomarker of Turbinaria conoides (J. Agardh) Kützing from South Pacific Islands. Issue 6 (16th October 2014) - Le Lann, Klervi; Kraffe, Edouard; Kervarec, Nelly; Cerantola, Stéphane; Payri, Claude Elisabeth; Stiger‐Pouvreau, Valérie; Verbruggen, H.
<x xml:space="preserve">Abstract</x> Several species of the genus Turbinaria coexist along the coasts of islands in the Indian and Pacific Oceans. Among these brown algae, Turbinaria ornata and T. conoides are sister species that are difficult to differentiate using exclusively morphological characters. Based on in vivo nuclear magnetic resonance and chromatographic techniques, i.e., liquid and gas chromatography‐mass spectrometry analysis, combined with phylogenetic data, we successfully identified turbinaric acid in T. conoides samples from several Indian and Pacific Ocean islands. This nonvariable discriminant molecule was only identified in T. conoides specimens, but not in the two allied species T. ornata and T. decurrens. Results are discussed with regard to turbinaric acid as an interesting chemomarker isolated from T. conoides and the rapid discrimination of Turbinaria specimens using chemical assays.